2021
DOI: 10.3389/fpsyt.2021.744341
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non-emergency Use of Control Interventions in Older Canadian Psychiatric Inpatients: Analysizing the InterRAI Mental Health Electronic Health Records

Abstract: Background: The use of control interventions (CIs; acute control medications, physical/mechanical restraint) is associated with negative physical and psychological outcomes, particularly in older adults who are physically vulnerable. The aims of this study were to: (i) report the rates of CI use in older psychiatric inpatients (age 65 – 84 and age 85+), and compare them with younger age groups (18 – 44, age 45 – 64); and (ii) identify the factors associated with non-emergency CI use in older psychiatric inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, a large Canadian study has shown that older psychiatric inpatients (age 65+) have higher rates of cognitive disorder, delirium, impaired self-care, falls and functional impairment than younger psychiatric inpatients (age<65). 8 Therefore, recording this as having 63 inpatient beds is inaccurate and will result in inadequate funding. Another example is West Coast where there is no POA inpatient bed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large Canadian study has shown that older psychiatric inpatients (age 65+) have higher rates of cognitive disorder, delirium, impaired self-care, falls and functional impairment than younger psychiatric inpatients (age<65). 8 Therefore, recording this as having 63 inpatient beds is inaccurate and will result in inadequate funding. Another example is West Coast where there is no POA inpatient bed.…”
Section: Discussionmentioning
confidence: 99%